Upaya Mengembangkan Kreativitas Belajar Siswa Kelas XI Melalui Layanan Bimbingan Belajar Di SMK Negeri 1 Lolowa’u - Luahambowo, Baspuri; Florina Laurence Zagoto, Sri (FATAWA: Jurnal Pendidikan Agama Islam, 2021)
This study aims to find out information about how to develop the learning creativity of class XI students through tutoring at SMK Negeri 1 Lolowa'u. According to the results of previous observations, efforts to develop learning creativity turned out to have a significant effect on tutoring. Based on these observations, the author tries to prove the truth through scientific research with the title: "Efforts to develop the learning creativity of class XI students at SMK Negeri 1 Lolowa'u". In this research activity, the authors limit the research to the following problem formulation: Can students' learning creativity be developed through Tutoring?. In solving the problem, the researcher tried as much as possible to process data related to the problem by choosing one of the data collection methods, namely a questionnaire both variable X and variable Y. The questionnaire was shown to students of SMK Negeri 1 Lolowa'u, especially class XI which had been determined as sample from this study. After the questionnaires were collected to students, the researchers processed them in accordance with the applicable steps of the research method, namely Verification of the questionnaire data that had been circulated to students, the authors carried out data processing through testing research tools and calculating the correlation coefficient between variable X and variable Y. Based on the processing the data that has been carried out is known that the results of data processing and analysis obtained a correlation coefficient of rxy = 0.769, while the price in the critical table r prodact moment = 0.367 it turns out that the rxy value obtained in this study is greater than the critical value of rt product moment, so that the hypothesis in this research is acceptable.